Stimulation and Repair of Peripheral Nerves Using Bioadhesive Graft‐Antenna. Issue 11 (3rd April 2019) - Sliow, Ashour; Ma, Zhi; Gargiulo, Gaetano; Mahns, David; Mawad, Damia; Breen, Paul; Stoodley, Marcus; Houang, Jessica; Kuchel, Rhiannon; Tettamanzi, Giuseppe C.; Tilley, Richard D.; Frost, Samuel J.; et al.
Abstract: An original wireless stimulator for peripheral nerves based on a metal loop (diameter ≈1 mm) that is powered by a transcranial magnetic stimulator (TMS) and does not require circuitry components is reported. The loop can be integrated in a chitosan scaffold that functions as a graft when applied onto transected nerves (graft‐antenna). The graft‐antenna is bonded to rat sciatic nerves by a laser without sutures; it does not migrate after implantation and is able to trigger steady compound muscle action potentials for 12 weeks (CMAP ≈1.3 mV). Eight weeks postoperatively, axon regeneration is facilitated in transected nerves that are repaired with the graft‐antenna and stimulated by the TMS for 1 h per week. The graft‐antenna is an innovative and minimally‐invasive device that functions concurrently as a wireless stimulator and adhesive scaffold for nerve repair. Abstract : A graft‐antenna is used as an innovative nerve stimulator consisting of a gold loop antenna integrated into a chitosan scaffold. The graft‐antenna is laser‐bonded to peripheral nerves and triggers compound action potentials (≈1.3 mV) when powered by radio waves transcranial magnetic stimulator (TMS). Axon regeneration is facilitated in transected nerves that are repaired with the graft‐antenna and stimulated 1 h per week by the TMS.